Attempt to correlate surface physics and chemical properties : molecular beam and Kelvin probe investigations of Ce 1-x Zr x O 2 thin films - Kolekar, Sadhu K.; Dubey, Anjani; Date, Kalyani S.; Datar, Suwarna; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2016)
What is the correlation between physical properties of the surfaces (such as surface potential, electronic nature of the surface), and chemical and catalysis properties (such as chemisorption, sticking probability of surface)? An attempt has been made to explore any correlation that might exist between the physical and chemical properties of thin film surfaces. Kelvin probe microscopy (KPM) and the molecular beam (MB) methods were employed to carry out the surface potential, and oxygen adsorption and oxygen storage capacity (OSC) measurements on Ce1−xZrxO2 thin films. A sol–gel synthesis procedure and spin-coating deposition method have been applied to make continuous nanocrystalline Ce1−xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (35–50 nm); however, surface roughness and porosity inherently changes with CZ composition. MB studies of O2 adsorption on CZ reveal high OSC for Ce0.9Zr0.1O2, which also exhibits highly porous and significantly rough surface characteristics. The surface potential observed from KPM studies varied between 30 and 80 mV, with Ce-rich compositions exhibiting the highest surface potential. Surface potential shows large changes after reduction or oxidation of the CZ film demonstrating the influence of Ce3+/Ce4+ on surface potential, which is also a key to catalytic activity for ceria-based catalysts. The surface potential measured from KPM and the OSC measured from MB vary linearly and they depend on the Ce3+/Ce4+ ratio. More and detailed studies are suggested to arrive at a correlation between the physical and chemical properties of the surfaces.

Ambient CO oxidation on in-situ generated Co3O4 spinel surfaces with random morphology - Dubey, Anjani; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ChemistrySelect, 2017)
The influence of the Co3O4 morphology on its redox behavior and catalytic performance in the CO oxidation reaction is studied. Three different Co3O4 morphologies were synthesized by precipitation and hydrothermal methods. TEM and SEM observations clearly show the different obtained morphologies: rods, wires and a mixture of plates and cubes. The textural properties depend on the morphology and the redox ones on the particle size. XRD analysis reveals a spinel structure in all solids but a preferential exposition of the [110] plane is presented in the Co3O4 rods. This preferential exposition, along with its higher specific surface area provides the rods with more efficient oxygen storage capacity resulting in an excellent catalytic performance compared to the other two morphologies.